PERBANDINGAN KINERJA KEUANGAN BANK MANDIRI DAN BCA DENGAN GRAND STRATEGY - Sukma, Komang Wisnu Angga; Ramantha, I Wayan (E-Jurnal Akuntansi; Vol 11 No 1 (2015), 2015)
This study aims to determine and compare the financial performance of Bank Mandiri and BCA in 2012 to see which better is. Measurement of financial performance seen from factors internal and external that is able to provide a snapshot of the financial performance of each bank in the banking industry. This study uses secondary data and observations obtained through non-behavior that is taken from a document in the form of financial statements, and the Indonesian banking statistics. Data analysis was performed by quantitative and qualitative analysis. Based on the results of the study found that the Bank Mandiri financial performance is better than the BCA. The weakness in this study was not to measure and look at the internal and external factors influence each bank every time and only focus in one analysize method. The surplus is an indicator used to assess the research object not only to the growth of profitability, but also on growth equity, growth in third-party funds, interest income growth, and the growth of the company's total assets which will provide a strategy that must be taken by the bank if the bank is located in the good health, reasonably healthy, less healthy, or unhealthy.
Keywords: Performance Assessment, Internal Factor